CONFLICT BETWEEN CUSTOMARY LAW AND HUMAN RIGHTS STANDARDS: A LITERATURE REVIEW OF CUSTOMARY PUNISHMENT PRACTICES AND GENDER EQUALITY ISSUES - Ika Dewi Sartika Saimima; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
This study examines the conflict between customary law and human rights standards, focusing on the practice of customary punishment and gender equality issues through a literature review method. Customary law, which is deeply rooted in community traditions, often conflicts with human rights principles that demand the protection of individual rights without discrimination, especially in the implementation of customary punishments that can violate the rights to freedom and physical integrity. In addition, the patriarchal structure of customary law creates gender inequality that hinders the rights of women and other gender groups in various aspects of life. This study presents a critical analysis of existing literature to understand the dimensions of this conflict and find common ground between local cultural norms and universal human rights principles. The results of the study indicate the need for inclusive and dialogical reform of customary law, respecting local wisdom without neglecting human rights, as an effort towards a fair, inclusive, and sustainable legal system.